1-Methylcyclopropene Modulates Physiological, Biochemical, and Antioxidant Responses of Rice to Different Salt Stress Levels - Hussain, Sajid; Bai, Zhigang; Huang, Jie; Cao, Xiaochuang; Zhu, Lianfeng; Zhu, Chunquan; Khaskheli, Maqsood Ahmed; Zhong, Chu; Jin, Qianyu; Zhang, Junhua (Frontiers in Plant Science, 2019)
Salt stress in soil is the key constraint affecting rice production. Salt stress hinders the plant growth by osmotic stress, ionic, and hormonal imbalance specially ethylene and therefore, thoughtful efforts are needed to devise management strategies for salt tolerance. In this study, we have attempted to induce salt tolerance in rice (Oryza sativa L.) cultivars by applying ethylene action inhibitor such as 1-methylcyclopropene (1-MCP). 1-Methylcyclopropene under salt stress modulates physiological, biochemical and antioxidants features of rice have not been studied before by any researcher. A pot culture experiment was conducted in a rainout shelter during rice growing season (2016 and 2017). For this purpose, two rice cultivars, Nipponbare (NPBA) and Liangyoupeijiu (LYP9), were exposed to four levels of salt 0 g (control, CK), 1.5 g (Low Salt Stress, LS), 4.5 g (Medium Salt Stress, MS), and 7.5 g of NaCl/kg dry soil (Heavy Salt Stress, HS). The average corresponding EC of soil was 0.12 dS m-1. Two levels of 1-MCP such as 0 g (CT) and 0.0214 g/pot (1-MCP) to acquire vital indicators of stress for management purposes were applied at the rice booting stage in 2016 and 2017. The results showed that 1-MCP significantly reduced ethylene production by 40.2% and 23.9% (CK), 44.3% and 28.6% (LS), 28% and 25.9% (MS) in both cultivars respectively, and 27.4% (HS) in LYP9 spikelets compared with no 1-MCP. 1-MCP improved photosynthesis rate (Pn) and SPAD values, in both rice cultivars. While it improved the superoxide dismutase (SOD) production, protein synthesis chlorophyll contents (chl a, b, carotenoids), and decreased malondialdehyde (MDA), H2O2, and proline accumulation in leaves. However, NPBA seedlings died at the HS level. 1-MCP also modulated aboveground biomass and grain yield per plant by 19.4% and 15.1% (CK), 30.3% and 24% (LS), 26.4% and 55.4% (MS) in both cultivars respectively, and 34.5% (HS) in LYP9 at maturity compared with no 1-MCP. However, the LYP9 cultivar showed better tolerance than the NPBA cultivar. Consequently, the results revealed that 1-MCP can be employed to modulate plant physiology, and biochemical, and antioxidant activities in rice at different salt stress levels as a salt stress remedy.